Topics in field theory - Karpilovsky, Gregory, 1940- (North-Holland mathematics studies, 1989)
This monograph gives a systematic account of certain important topics pertaining to field theory, including the central ideas, basic results and fundamental methods. Avoiding excessive technical detail, the book is intended for the student who has completed the equivalent of a standard first-year graduate algebra course. Thus it is assumed that the reader is familiar with basic ring-theoretic and group-theoretic concepts. A chapter on algebraic preliminaries is included, as well as a fairly large bibliography of works which are either directly relevant to the text or offer supplementary material of interest.